Readings in educational psychology - Bernard, Harold; Huckins, Wesley C. (Scranton, Pa. : International Textbook, 1967)
This book is designed for those students, so stimulating to professors, who seek to go beyond the satisfying of minimum requirements and are pursuing learning for their own sake. The Kinds of articles recommended in the past and endorsed by such students are the kinds contained within this volume.
I. The Field of education psychology -- II. The Nature and course of learning -- III. Educational implications of transfers -- IV. Problem solving and creativity -- V. Factors that facilitate learning -- VI. Language development -- VII. Growth and its relationship to learning -- VIII. The Nature and measurement of individual differences -- IX. The Nature and nature of intelligence -- X. Motivation of learning -- XI. Emotional aspects of education -- XII. Personality and its development -- XIII. The Child as a learner -- XIV. The Adolescent as a learner -- XV. Cultural influences- the role of the social setting -- XVI. Group processes in the classroom -- XVII. Programmed learning and autoinstruction -- XVIII. Mental hygiene as an aspect of educational psychology -- XIX. Teacher personality as a factor in learning -- XX. Evaluating for future growth.
Includes bibliographical references and index.
Keywords: EDUCATIONAL PSYCHOLOGY